1965
DOI: 10.1182/blood.v26.4.500.500
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Factor VIII by Thrombin

Abstract: The activation of human factor VIII by thrombin has been demonstrated by a new experimental approach. This method permitted investigation of the interaction of thrombin and factor VIII in the absence of most other clotting factors. The activation effect of thrombin is susceptible to inhibition by diisopropylfluorophosphate. Trypsin cannot replace thrombin in the activation reaction, and it destroys factor VIII activity rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1968
1968
1994
1994

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thrombin has been reported to increase the coagulant activity of factor VIII (Rapaport et al, 1963(Rapaport et al, , 1965Macfarlane et al, 1964;Ozge-Anwar et al, 1965;Legaz et al, 1973Legaz et al, , 1975Shapiro et al, 1973). Factor Xa has also been shown to result in the activation of factor VIII .…”
Section: Resultsmentioning
confidence: 99%
“…Thrombin has been reported to increase the coagulant activity of factor VIII (Rapaport et al, 1963(Rapaport et al, , 1965Macfarlane et al, 1964;Ozge-Anwar et al, 1965;Legaz et al, 1973Legaz et al, , 1975Shapiro et al, 1973). Factor Xa has also been shown to result in the activation of factor VIII .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there is no equivalent for the anti-Xa test system in the in vivo experiments. Second, it has been shown that even small amounts of Ila can activate various coagulation proteases such as F V, F VIII, F VII and F XI resulting in massive feedback coagulation activation (25)(26)(27)(28)(29)(30). Suppression of Ila generation either by inhibition of Xa by LMWH or of Ila by UFH may cause a marked reduction of Ila-induced feedback activation of the coagulation system and, subsequently, a (possibly comparable) reduction ofF 1 + 2 , TAT and FPA generation.…”
Section: Discussionmentioning
confidence: 99%
“…The substrates for these assays were plasmas congenitall y deficient in these factors 1 ) or artificially depleted with celite. Normal PPP and that deficient in factor XII was collected and processed as describ ed before (32). Normal PPP was rendered deficient in factor XI by adsorption with 6 mg Celite 512 per m l plasma, or exh austed of factors XII and XI by adsorption with 50 mg/ml according to Nossel (30).…”
Section: Clotting T Estsmentioning
confidence: 99%